Effect of Hemodialysis and Peritoneal Dialysis on some Hematological and Biochemical Parameters in Renal Failure - Mohammad, Dara Khorshed (Zanco Journal of Medical Sciences (ZJMS), 2009)
Background and objective: The purpose of the present study was to determine the effects of hemodialysis and peritoneal dialysis on some hematological and biochemical parameters in patients with renal failure on the dialysis. Methods: Fifty two patients with renal failure were taken in this experiment on dialysis studied in the dialysis and kidney disease center in hawler teaching hospital, twenty six patients were taken for haemodialysis and the remaining patients were taken for the peritoneal dialysis process. Some hematological and biochemical parameters were taken before and after dialysis. Results: In the Hemodialysis Patients: Hemoglobin concentration (Hb gm/dl), Red blood cells (RBCs x106/μl) and packed cell volume (PCV %) count, blood sugar (mg/dl), serum calcium (mg/dl), serum sodium (meq/L) and serum potassium (meq/L) were high significantly increased in patient with renal failure after hemodialysis in comparison before hemodialysis, while blood urea (mg/dl) were high significantly decreased in patient with renal failure after hemodialysis in comparison before hemodialysis. In the Peritoneal dialysis patients: Hb (gm/dl) and PCV (%) count, blood sugar (mg/dl) and serum calcium (mg/dl) were high significantly increased in patient with renal failure after peritoneal dialysis in comparison before peritoneal dialysis, while blood Urea (mg/dl) and serum Creatinine (mg/dl) were high significantly decreased in patient with renal failure after peritoneal dialysis in comparison before peritoneal dialysis, while there were non significant differences in serum sodium (meq/L) before and after peritoneal dialysis. Conclusion: Hemodialysis significantly increases some RBC, Hb and PCV. Hemodialysis cause significantly decreases blood sugar and urea. Peritoneal dialysis significantly increases PCV and Hb. Peritoneal dialysis cause decreases the blood urea and blood sugar. Hemodialysis was more useful and gives good results than peritoneal dialysis.